Factores asociados con la intensidad del dolor en pacientes mexicanos hospitalizados en periodo postoperatorio - Moreno Monsiváis, María Guadalupe; Fonseca Niño, Elvia Elena; Interial Guzmán, María Guadalupe (2016)
ABSTRACT Objective: To determine the association between the pain intensity (assessment) reported by the hospitalized postoperative mexican patients with some features of patient and nursing staff. Material and methods: The study design was descriptive and correlational. The sample consisted of 231 patients selected through a systematic sampling of one in two with random start, 31 nurses representing the total of nurses who work in the departments of general surgery, orthopedics and gynecology were included. For data collection the patient data certificate, nurse identification card, pain intensity (assessment) questionnaire to postoperative patient and pain awareness survey for nursing were used. Results: A high proportion of patients had moderate to severe pain during the first 24 postoperative hours, 69.6 % of participants had severe pain. No association between pain intensity (assessment) with age and education of the patient, or the knowledge of nurses about pain management were found. Significant difference was found in pain intensity about sex, pain experienced at maximum (U = 3997.50, p = 0.001) and average pain over 24 hours (U = 4852, p = 0.03).The more intensity (assessment) of pain was located in the female. The average of nursing staff knowledge regarding pain management stood at 54.40 (SD = 13.12). The average intensity (assessment) of pain experienced by the patient in the first 24 hours was associated with the number of patients assigned to nurses (rs = 0.167, p = 0.01). Conclusions: Pain management in postoperative period is inappropriate and remains a challenge to national and international trend to have pain-free hospitals. It is recommended as a measure to contribute to pain relief, consider the appropriate pharmacological management to the demands of the patient, the use of non-pharmacological measures, assessment of pain intensity and its effects regularly and education that the patient is provided. Key words: Postoperative pain, pain management, pain assessment, hospitalization, nursing staff.